Sturge-Weber syndrome - Natarajan Manivannan; Subramanium Gokulanathan; Ramakrishnan Swamy Ahathya; Gubernath; Rajkumar Daniel; Shanmugasundaram (Wolters Kluwer Medknow Publications, 2012)
Encephalotrigeminal angiomatosis (Sturge-Weber syndrome) is a rather uncommon congenital condition characterized by the combination of venous angioma of the leptomeninges over the cerebral cortex with ipsilateral angiomatous lesions of the face, and sometimes the skull, jaws, and oral soft tissues. A case of portwine stain with intraoral gingival hemangioma is presented. There were no other systemic manifestations. Patient reported with a complaint of localized tumor-like swelling in gums. Based on the presence of sharply demarcated vascular lesion unilaterally on the face and with ipsilateral intraoral vascular hyperplasia in the lip and gingiva, a variant of encephalotrigeminal angiomatosis was diagnosed. Ultrasound Doppler flowmetry was used to determine the blood flow. Dental management included plaque control instructions, scaling, root planning, and excision of the lesion done under general anesthesia. Close follow-up and meticulous plaque control have kept the oral condition under fairly good control.